Rubber Development of Sustainable in Indonesia - SABARMAN DAMANIK (Puslitbang Perkebunan, 2012)
Prospect of sustainable rubber development is one of the important factors determining investment in rubber plantations as thikind of investment is a long term one. In according with this issue, area , production, consumption, trade, an price of rubber , either in term of international or national perspective are discussed. World production an consumption are projected to increase at the same growth rate that is at 2,5 % annual growth rate. World trade a projected to increase by 2,6/cent/annum, while rubber price is estimated to lie between USS 1,2 – 1,5 per kg in the next decade. Based on these figures and with a moderate scenario. Indonesia is estimated to have a opportunity to increase rubber production and export by 2,2% per annum, respectively. To capture these opportunities, Indonesia still faces some problems in relation to low productivity and product quality The overcame these problems, same polities are also proposed within this study. Keywords : Rubber development, product, quality, sustainable